2003
DOI: 10.1086/374687
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale Structure of the SN 1006 Shock withChandraObservations

Abstract: The northeast shell of SN 1006 is the most probable acceleration site of high-energy electrons (up to $100 TeV) with the Fermi acceleration mechanism at the shock front. We resolved nonthermal filaments from thermal emission in the shell with the excellent spatial resolution of Chandra. The thermal component is extended over $100 00 (about 1 pc at 1.8 kpc distance) in width, consistent with the shock width derived from the Sedov solution. The spectrum is fitted with a thin thermal plasma of kT ¼ 0:24 keV in no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
351
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(398 citation statements)
references
References 34 publications
(38 reference statements)
43
351
1
Order By: Relevance
“…This is compatible with the Chandra data, as shown by Berezhko et al (2003). Bamba et al (2003) reported a much smaller scale height upstream, but this was based on the mistaken assumption that there should be no emissivity jump at the shock. Berezhko et al (2002) argue that the bright limbs are polar caps where the magnetic field (far upstream) is parallel to the shock speed.…”
Section: The Polar Cap Modelsupporting
confidence: 88%
See 3 more Smart Citations
“…This is compatible with the Chandra data, as shown by Berezhko et al (2003). Bamba et al (2003) reported a much smaller scale height upstream, but this was based on the mistaken assumption that there should be no emissivity jump at the shock. Berezhko et al (2002) argue that the bright limbs are polar caps where the magnetic field (far upstream) is parallel to the shock speed.…”
Section: The Polar Cap Modelsupporting
confidence: 88%
“…This is supported by the very thin filaments observed by Chandra (Bamba et al 2003), whose width is probably limited by radiative losses.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…This can lead to strong modifications of the shock structure and a nonlinear coupling between the shock flow and CR acceleration. Some observational results are consistent with the predictions of such nonlinear DSA (NLDSA) models (Bamba et al 2003(Bamba et al , 2005a2005b, Vink & Laming 2003Warren et al 2005;Uchiyama et al 2007;Helder et al 2009). However, whether these models can fully explain all aspects revealed by the accumulating multiwavelength observations still remains in doubt.…”
Section: Origin Of Galactic Cosmic Rayssupporting
confidence: 79%